Implementation of Supreme Court Regulation Number 3 of 2022 concerning Electronic Court Mediation at the Pekalongan Religious Court - Anggreini Gema Dzikrillah; Dian Latifiani (Semarang State University Undergraduate Law and Society Review, 2025)
This study aims to analyze the implementation of Supreme Court Regulation (PERMA) Number 3 of 2022 concerning Mediation in Courts, especially in the implementation of electronic mediation at the Pekalongan Religious Court. This research uses an empirical approach with data collection techniques through interviews with mediator, judges and clerks. The results showed that electronic mediation has been implemented since 2023, although with a limited number of cases. Pekalongan Religious Court has supporting facilities such as television, sound system, and microphone, but there is no special technical training for mediators. The main obstacles in the implementation of electronic mediation include limited internet networks, uneven technological devices, and varying levels of digital literacy of the parties. In addition, there is no specific administration to support the optimal implementation of electronic mediation. Nevertheless, electronic mediation remains an efficient alternative in certain cases, such as disputes with parties domiciled far from the trial location. This research recommends the need for training for mediators, strengthening digital infrastructure, and continuous socialization to the community to support the effective implementation of electronic mediation in accordance with the spirit of PERMA Number 3 of 2022.